1995
DOI: 10.1063/1.114401
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence study of the crossover from two-dimensional to three-dimensional growth for Ge on Si(100)

Abstract: Narrow Ge layers embedded in Si are investigated using photoluminescence (PL) spectroscopy. With increasing layer thickness a growth mode changeover from two-dimensional (2D) strained-layer growth to three dimensional Stranski–Krastanov growth is observed. Additional PL lines that are redshifted with respect to the PL signal of the 2D strained layers are attributed to islands formed by three-dimensional growth. The occurrence of these new lines is accompanied by a blueshift of the PL of the 2D layers, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(87 citation statements)
references
References 0 publications
6
81
0
Order By: Relevance
“…The exciting applications of nanosize islands, as well as their fundamentally interesting electronic and structural properties, have motivated many research groups to study island formation, attempting to understand the kinetic and thermodynamic factors determining the self-assembly process. Islands form spontaneously in many heteroepitaxial systems where the mismatch is large (above 1-2%), including InP/GaInP, InGaAs/GaAs and CdSe/ZnSe (Bennett et al, 1996;Carlsson et al, 1994;Ferrer et al, 1996;Kobayashi et al, 1996;Leon et al, 1995Leon et al, , 1997Leonard et al, 1993Leonard et al, , 1994Lubyshev et al, 1996;Madhukar et al, 1994;Moison et al, 1994;Ponchet et al, 1995;Reaves et al, 1996;Ruvimov et al, 1995;Snyder et al, 1991;Solomon et al, 1995Solomon et al, , 1996Xie et al, 1996;Xin et al, 1996), as well as Si/Ge and Ge/Si (Chen et al, , 1997Cunningham et al, 1991;Deelman et al, 1996;Eaglesham and Cerullo, 1990;Floro et al, 1997;Goryll et al, 1997;Hansson et al, 1993;Kamins et al, 1997;Knall and Pethica, 1992;Kohler et al, 1991;Krishnamurthy et al, 1991a,b;Maree et al, 1987;Medeiros-Ribeiro et al, 1998;Mo et al, 1990;Sakai and Tatsumi, 1993;Schittenhelm et al, 1995;Sumitomo et al, 1995a,b;…”
Section: Introductionmentioning
confidence: 97%
“…The exciting applications of nanosize islands, as well as their fundamentally interesting electronic and structural properties, have motivated many research groups to study island formation, attempting to understand the kinetic and thermodynamic factors determining the self-assembly process. Islands form spontaneously in many heteroepitaxial systems where the mismatch is large (above 1-2%), including InP/GaInP, InGaAs/GaAs and CdSe/ZnSe (Bennett et al, 1996;Carlsson et al, 1994;Ferrer et al, 1996;Kobayashi et al, 1996;Leon et al, 1995Leon et al, , 1997Leonard et al, 1993Leonard et al, , 1994Lubyshev et al, 1996;Madhukar et al, 1994;Moison et al, 1994;Ponchet et al, 1995;Reaves et al, 1996;Ruvimov et al, 1995;Snyder et al, 1991;Solomon et al, 1995Solomon et al, , 1996Xie et al, 1996;Xin et al, 1996), as well as Si/Ge and Ge/Si (Chen et al, , 1997Cunningham et al, 1991;Deelman et al, 1996;Eaglesham and Cerullo, 1990;Floro et al, 1997;Goryll et al, 1997;Hansson et al, 1993;Kamins et al, 1997;Knall and Pethica, 1992;Kohler et al, 1991;Krishnamurthy et al, 1991a,b;Maree et al, 1987;Medeiros-Ribeiro et al, 1998;Mo et al, 1990;Sakai and Tatsumi, 1993;Schittenhelm et al, 1995;Sumitomo et al, 1995a,b;…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that dislocation-free SiGe growth can be achieved using a higher temperature (≥600°C), and that the non-planar geometry is mainly responsible for the significant increase of the SiGe critical layer thickness. It has also been found that, compared to two-dimensional (2D) Si/SiGe NSs, the PL and EL quantum efficiency in 3D Si/SiGe NSs is higher (up to 1%), especially for T > 50 K (Cerdeira et al, 1972;Apetz et al, 1995;Schittenhelm et al, 1995;Schmidt et al, 1999b). Despite many successful demonstrations of PL and EL in the spectral range of 1.3-1.6 μm, which is important for optical fiber communications, the proposed further development of 3D Si/SiGe-based light emitters was discouraged by several studies, indicating a type II energy band alignment at Si/SiGe heterointerfaces (Van de Walle and Martin, 1986;Thewalt et al, 1997;Schittenhelm et al, 1998;El Kurdi et al, 2006), where the spatial separation of electrons (located in Si) and holes (localized in SiGe) (see 1) was thought to make carrier radiative recombination very inefficient.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…It has been shown that dislocation-free SiGe growth can be achieved using a higher temperature (≥600 o C), and that the non-planar geometry is mainly responsible for the significant increase of the SiGe critical layer thickness [5]. It has also been found that, compared to two-dimemensional (2D) Si/SiGe NSs, the PL and electroluminescence (EL) quantum efficiency in 3D Si/SiGe NSs is higher (up to ~1%), especially for T > 50 K [6][7][8][9]. Despite many successful demonstrations of PL and EL in the spectral range of 1.3-1.6 m, which is important for optical fiber communications, the proposed further development of 3D Si/SiGe based light emitters was discouraged by several studies indicating a type II energy band alignment at Si/SiGe heterointerfaces [10], where the spatial separation of electrons (located in Si) and holes (localized in SiGe) was thought to make carrier radiative recombination very inefficient.…”
mentioning
confidence: 91%